Techno-economic analysis of grid connected PV-battery system in Sarawak, Malaysia - Yap, Yu Vun (2022)
Nowadays, energy use has become a very critical concern because of rapid increase in energy demand. The increased concerns for environmental impacts of conventional fossil fuels most importantly those related to global warming have been the major aspect driving the transformation towards green energy. However, the implementation of photovoltaic (PV) systems in Sarawak, East Malaysia, is still weak and has yet to be a common practice in Sarawak’s construction industry. Furthermore, very limited research studies have been carried out to analyse the techno-economic feasibility of grid-connected PV-battery systems, especially in Sarawak. The main purpose of this study was to analyse the feasibility of grid-connected PV-battery systems to be implemented in towns of Sarawak, East Malaysia. This study also aimed to investigate the Levelized Cost of Energy (LCOE) and Net Present Cost (NPC), analyse the carbon emissions and determine the potentiality of the system. The proposed system will took into account several constraints such as the technical, economics and environmental impact of grid-connected PV battery system. The Hybrid Optimization of Multiple Energy Resources (HOMER) software was used to perform the simulation work to determine the economic and environmental effects and evaluate the feasibility of the proposed system in the towns of Sarawak. In addition, the technical features of the grid-connected PV-battery system were analysed using MATLAB/Simulink software.